(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Over the past several decades, tourism has become a key sector in the world economy, making it a critical source of economic growth and development in many countries. Tourists depend in their search for destinations and travel-buying process on many sources including brochures, which are of great significance for both tourists and tourist agencies. The study attempts to underline the role of culture and the influence of stylistic differences between the languages on handling English and Arabic tourist brochures in translation. After integrating quantitative measurement and qualitative analysis and discussing the findings for four translated brochures, the study has found significant differences in the distribution of vocabulary which can be said to result from the difference in the style of prose writing in the two languages which is to a large extent determined by situations. Also the findings indicate that Arabic texts tend to use more coordinated sentences than English texts do. This goes in line with the claim that coordination is salient feature of Arabic style.